2017
DOI: 10.1136/rmdopen-2016-000353
|View full text |Cite
|
Sign up to set email alerts
|

Is vascular endothelial growth factor a useful biomarker in giant cell arteritis?

Abstract: ObjectivesTo assess the performance of circulating vascular endothelial growth factor (VEGF) levels as a tool for diagnosing giant cell arteritis (GCA) in a cohort of patients referred for assessment of suspected GCA.MethodsWe selected 298 patients recruited to the multicentre study Temporal Artery Biopsy versus Ultrasound in diagnosis of suspected GCA (TABUL). In a random subset of 26 biopsy-proven GCA cases and 26 controls, serum from weeks 0, 2 and 26 was analysed for VEGF concentration using ELISA. VEGF co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
(47 reference statements)
1
9
1
Order By: Relevance
“…Pentraxin 3 has been proposed as a useful biomarker in GCA due to the fact that it is both an acute phase reactant and is elevated in non‐inflammatory vascular injury states and atherosclerosis 14,24 . Our negative results are in keeping with the findings of Goodfellow et al which required serum to be collected within 7 days of corticosteroids 9 . It contrasts with the positive findings of an earlier cohort of long‐term GCA patients where pentraxin 3 levels were higher for GCA than healthy controls and rheumatoid arthritis patients 14 …”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Pentraxin 3 has been proposed as a useful biomarker in GCA due to the fact that it is both an acute phase reactant and is elevated in non‐inflammatory vascular injury states and atherosclerosis 14,24 . Our negative results are in keeping with the findings of Goodfellow et al which required serum to be collected within 7 days of corticosteroids 9 . It contrasts with the positive findings of an earlier cohort of long‐term GCA patients where pentraxin 3 levels were higher for GCA than healthy controls and rheumatoid arthritis patients 14 …”
Section: Discussionsupporting
confidence: 88%
“…A number of studies have found VEGF to be elevated in GCA patients and those with rheumatic diseases 25 compared with normal controls 9,14 . VEGF is a growth factor that stimulates angiogenesis in chronic inflammatory states and promotes the migration of monocytes and lymphocytes into the extracellular matrix 8,26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings highlight the importance of new vessel formation at the site of inflammation in GCA to fuel the ongoing inflammatory process and are in line with previous studies reporting on elevated levels of VEGF in GCA. However, these studies did not investigate this marker in longitudinal follow-up studies [25, 30, 31].…”
Section: Discussionmentioning
confidence: 99%
“…During inflammation, monocytes/macrophages also release calprotectin, sCD163 and YKL-40 [22–24]. Inflamed GCA vessels are characterized by new vessel formation involving VEGF, angiopoietin-1 and -2 and sTie2 as key regulators in this process [25–27].…”
Section: Introductionmentioning
confidence: 99%